DISTRIBUTION AND DIVERSITY OF BUTTERFLIES (Lepidoptera: Rhopalocera) IN CAMPUS AREA INDRALAYA SRIWIJAYA UNIVERSITY OF SOUTH SUMATRA - Lamin, Syafrina; Sari, Nirmila; Setiawan, Doni (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2016)
Research on Diversity and distribution of butterflies, was held at the Campus Indralaya Sriwijaya University of South Sumatra. The purpose of this study was to obtain information species diversity of butterflies at the Sriwijaya University of Inderalaya and distribution of species of butterflies in several different habitat types in the campus area Unsri Indralaya. The study used purposive and collection methods in November 2014-january 2015. Sampling sites were divided into five locations: Arboretum, Science Faculty, Faculty of Law, Faculty of Agriculture and Swamp Cape Disconnect. The parameters used are the index of species diversity, dominance index, and evenness index. The results showed that the diversity of butterflies in the region is classified as moderate. Overall found as many as 40 species of butterflies with a number of 609 individuals consisting of 5 the Papilionidae, Nymphalidae, Pieridae, Lycaenidae, and Hesperiidae. Regions Sriwijaya University has a diversity of butterflies that were moderate with criteria (H'1≤H'≤3), in each different habitat types, and not found butterfly species that dominate in every type of habitat in this Unsri region. Distribution of butterflies found in the campus area Unsri Indralaya categorized fairly evenly with a range of values from 0.58 to 0.68.Keywords: Butterflies, Diversity, Distribution , Sriwijaya University of Indralaya